Pengetahuan dan sikap remaja putri dalam mengelola dismenore primer - Fauziah, Nur Aeni Afiyah; Sulastri, Sulastri (Holistik Jurnal Kesehatan, 2025)
Background: Primary dysmenorrhea is a very common menstrual disorder in adolescent girls, characterized by painful menstruation without any organic abnormalities. This condition impacts school activities, productivity, and quality of life. Despite its high prevalence, many adolescents fail to manage this complaint effectively due to a lack of knowledge and poor attitudes. Appropriate management efforts are largely determined by personal understanding and perceptions of menstrual pain. Purpose: To analyze the relationship between adolescent girls' knowledge and attitudes in managing primary dysmenorrhea. Method: This descriptive correlational study used a cross-sectional approach. A sample of 100 eleventh-grade female students was selected using a total sampling technique. Data collection was conducted through a structured questionnaire that measured knowledge, attitudes, and practices in managing primary dysmenorrhea. Data were analyzed statistically using the Chi-Square test and Fisher's Exact Test with a significance level of p < 0.05. Results: The majority of respondents had adequate knowledge (69%), negative attitudes (56%), and good management (78%). Bivariate testing showed a significant relationship between knowledge and management of primary dysmenorrhea (p = 0.027) and attitudes and management of primary dysmenorrhea (p = 0.000). Conclusion: Knowledge and attitudes are significantly associated with management of primary dysmenorrhea. The importance of continuing reproductive health education in schools needs to be increased to support more effective and independent management of menstrual pain.   Keywords: Adolescent Girls; Attitudes; Knowledge; Primary Dysmenorrhea.   Pendahuluan: Dismenore primer merupakan gangguan menstruasi yang sangat umum pada remaja putri, ditandai dengan nyeri haid tanpa kelainan organik. Kondisi ini berdampak pada aktivitas sekolah, produktivitas, dan kualitas hidup. Meskipun prevalensinya tinggi, banyak remaja yang belum mengelola keluhan tersebut secara efektif karena kurangnya pengetahuan dan sikap yang kurang mendukung. Upaya penatalaksanaan yang tepat sangat ditentukan oleh pemahaman dan persepsi pribadi terhadap nyeri haid. Tujuan: Untuk menganalisis hubungan antara pengetahuan dan sikap remaja putri dalam mengelola dismenore primer. Metode: Penelitian deskriptif korelasional dengan pendekatan cross-sectional. Sampel berjumlah 100 siswi kelas XI diambil menggunakan teknik total sampling. Pengumpulan data dilakukan melalui kuesioner terstruktur yang mengukur pengetahuan, sikap, dan praktik penanganan dismenore primer. Data dianalisis secara statistik menggunakan uji Chi-Square dan Fisher’s Exact Test dengan batas kemaknaan p < 0,05. Hasil: Mayoritas responden memiliki pengetahuan cukup (69%), sikap negatif (56%), dan penanganan yang baik (78%). Uji bivariat menunjukkan adanya hubungan signifikan antara pengetahuan dengan penanganan dismenore primer (p = 0.027) serta sikap dengan penanganan dismenore primer (p = 0.000). Simpulan: Pengetahuan dan sikap secara signifikan berhubungan dengan penatalaksanaan dismenore primer. Pentingnya edukasi kesehatan reproduksi berkelanjutan di lingkungan sekolah perlu ditingkatkan guna mendukung manajemen nyeri haid yang lebih efektif dan mandiri.   Kata Kunci: Dismenore Primer; Pengetahuan; Remaja Putri; Sikap.